2015
DOI: 10.1101/cshperspect.a006023
|View full text |Cite
|
Sign up to set email alerts
|

Signaling in Muscle Contraction

Abstract: SUMMARYSignaling pathways regulate contraction of striated (skeletal and cardiac) and smooth muscle. Although these are similar, there are striking differences in the pathways that can be attributed to the distinct functional roles of the different muscle types. Muscles contract in response to depolarization, activation of G-protein-coupled receptors and other stimuli. The actomyosin fibers responsible for contraction require an increase in the cytosolic levels of calcium, which signaling pathways induce by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
216
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(242 citation statements)
references
References 61 publications
1
216
0
Order By: Relevance
“…Previous studies have demonstrated that imiquimod induces rises in [Ca 2ϩ ] i in sensory neurons (24), and PC12 and F11 cell lines (20), with the latter study highlighting a role for the inositol triphosphate (IP 3 ) receptor activation in this process. Contractions by histamine and carbachol, both of which were reversed by imiquimod, primarily rely on IP 3 signaling and release of ERderived Ca 2ϩ to induce contraction (25). Imiquimod may disrupt this pathway either through binding to and blocking the IP 3 receptor (19), or emptying of ER pools, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated that imiquimod induces rises in [Ca 2ϩ ] i in sensory neurons (24), and PC12 and F11 cell lines (20), with the latter study highlighting a role for the inositol triphosphate (IP 3 ) receptor activation in this process. Contractions by histamine and carbachol, both of which were reversed by imiquimod, primarily rely on IP 3 signaling and release of ERderived Ca 2ϩ to induce contraction (25). Imiquimod may disrupt this pathway either through binding to and blocking the IP 3 receptor (19), or emptying of ER pools, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Increased intracellular free Ca 2+ concentration ([Ca 2+ ] i ) is essential for the activity of Nox5,18, 19, 20 as evidenced in cell‐culture studies where ROS are not synthesized in Ca 2+ ‐free buffer or from cells with truncation of the N‐terminal region of Nox5 21. This is of particular significance in vascular smooth muscle cells (VSMCs), given that increased [Ca 2+ ] i is the major trigger for vascular contraction 22, 23. Nox5 is expressed in all vascular cell types, including endothelial cells, VSMCs, and perivascular adventitial fibroblast,12, 14, 24 and plays a role in angiotensin II (Ang II)‐ and endothelin‐1 (ET‐1)‐mediated redox signaling 25.…”
mentioning
confidence: 99%
“…However, there are no studies to support the association of smaller genes with skin development. The categorization on the basis of published work has its advantages, but there is often overlapping of functions within these categories, for example, calcium signalling also happens in the muscle [84] and immune system [85], Wnt signalling pathway also has a role in cancer [86], TGF-beta signalling pathway can also be associated with the immune system [87], among others. In spite of this, our findings lead us to believe there is a disparity in gene sizes for genes that have a role or are present in tissues with very little to almost no development pos-natally (like neuron) and genes (not involved in housekeeping) that are quite frequently expressed during a human’s whole lifetime (like in skin development and immune response) or involved in providing functions with fast responses.…”
Section: Discussionmentioning
confidence: 99%